2002
DOI: 10.1038/nature01100
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism of a graphite nodule from the Canyon Diablo meteorite

Abstract: There are recent reports of weak ferromagnetism in graphite and synthetic carbon materials such as rhombohedral C(60) (ref. 4), as well as a theoretical prediction of a ferromagnetic instability in graphene sheets. With very small ferromagnetic signals, it is difficult to be certain that the origin is intrinsic, rather than due to minute concentrations of iron-rich impurities. Here we take a different experimental approach to study ferromagnetism in graphitic materials, by making use of meteoritic graphite, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
152
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(158 citation statements)
references
References 16 publications
5
152
1
Order By: Relevance
“…However, minor amounts of magnetite, kamacite, etc, also appear in their graphite samples [2]. These secondary phases are responsible for about two-thirds of the observed magnetization and the remaining one-thirds is attributed to the graphite-nodule.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, minor amounts of magnetite, kamacite, etc, also appear in their graphite samples [2]. These secondary phases are responsible for about two-thirds of the observed magnetization and the remaining one-thirds is attributed to the graphite-nodule.…”
Section: Introductionmentioning
confidence: 99%
“…The last point was firstly proposed by Coey et al, who suggested to measure a bulk graphite-nodule to gain a large ferromagnetic signal [2]. However, minor amounts of magnetite, kamacite, etc, also appear in their graphite samples [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent experiments suggest that pure graphite behaves as a highly correlated electron system [1]. In particular it shows a metalinsulator transition in magnetic fields and insulating behavior in the direction perpendicular to the planes in different samples [1,2,3,4,5,6,7,8]. Recent results show ferromagnetic behavior [9], enhanced by proton bombardment [10], what opens up a new way to the creation of organic magnets [11].…”
mentioning
confidence: 99%
“…We found that by doping boron and nitrogen the semiconductor gap, E g , of a zigzag SWCNT could be control 8 . It is shown that vacancy could lead to electron spin polarization, hence a magnetic SWCNT 9,10 . But role of doping finite magnetic impurity concentration on a zigzag SWCNT is not challenged.…”
Section: Introductionmentioning
confidence: 99%